3 The use of online videoconferencing for focus groups in palliative care research. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Gemmell, Rebecca; Allam, Alison; Perkins, Margaret; Droney, Joanne
Abstract : Background: Qualitative focus group research traditionally involves participants meeting face-to-face- in small groups to allow for participant interaction. The Covid-19 pandemic has prevented such meetings. Consequently, research has moved to holding online meetings using videoconferencing software. We discuss the advantages and challenges of running such groups. Method: We ran two focus groups on early palliative care in haemato-oncology using the videoconferencing platform Zoom. Recruitment was conducted online using pre-existing mailing lists and in person within the hospital outpatient department. Potential participants were emailed information about the focus of the discussion, . before signing a consent form returned by post or email. Groups were audio recorded with the consent of participants and transcribed for analysis. Results: One person declined to participate due to the group's online setting. Four and eight participants respectively attended the groups, each led by a lead facilitator and two PPI co-facilitators. Participants conversed openly, using hand raising to indicate when they wanted to speak. Conversation did not appear hindered by the online setting. Participants commented that they felt able to interact easily on the virtual platform even when discussing highly emotive issues; in-depth discussion of the chosen topic was achieved. Participants thought that some participants may be deterred from participation in online videoconferencing; one person declined to participate due to the group's online setting. The virtual platform enabled participants from a wide age range and geographical location to participate. There were no significant technical challenges. One person declined to participate due to the group's online setting. Conclusion: Online videoconferencing is increasingly common in professional and social settings due to the Covid-19 pandemic. It can be used effectively in qualitative research. Choice of platform, recruitment methods, obtaining valid consent, and recording the meeting need to be carefully considered. Researchers and participants should be supported to engage with technology to support robust research but consideration must be given to several factors to ensure success.